Reconciling Ownership Conflict Between Fiduciary Security and Leasing Law in Indonesia - Tajuddin Noor; Suhaila Zulkifli (Faculty of Law, University of Mataram, 2026)
The rapid expansion of Indonesia’s financing sector has intensified the use of leasing as an alternative to conventional credit systems. However, the integration of fiduciary security into leasing arrangements has generated a fundamental legal inconsistency concerning ownership. Under leasing law, ownership of the leased asset remains with the lessor during the contract period, whereas fiduciary law requires the debtor to possess ownership of the secured object. This study aims to examine and reconcile the ownership conflict between fiduciary security and leasing law in Indonesia.This research employs a normative juridical method using statutory, conceptual, and comparative approaches. Legal materials consist of primary sources, including Law No. 42 of 1999 on Fiduciary Security and Minister of Finance Regulation No. 84/PMK.012/2006, as well as secondary sources such as legal doctrines and scholarly literature.The findings reveal that the current application of fiduciary guarantees in leasing agreements creates a legal paradox, as lessees are not the legal owners of the leased assets but are positioned as fiduciary providers. This inconsistency results in legal uncertainty, weak enforceability, and imbalance in the rights and obligations of the parties. To address this issue, this study proposes a normative reconstruction by clarifying the separation between ownership under leasing and fiduciary security. Fiduciary guarantees should only be imposed on assets legally owned by the lessee, while the leased object remains under the ownership of the lessor until the end of the contract term.This study contributes to the development of Indonesian financial law by offering a coherent legal framework to resolve ownership conflicts between fiduciary security and leasing practices, thereby enhancing doctrinal clarity and regulatory consistency.